2022
DOI: 10.1111/epi.17188
|View full text |Cite
|
Sign up to set email alerts
|

A de novo missense variant in GABRA4 alters receptor function in an epileptic and neurodevelopmental phenotype

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Shank3 gene expression was significantly increased following 20 Gy, which could suggest increased neurotransmission [ 82 ]. Gabra4 and Gabra5 both contribute to inhibitory synapses signaling in neurons [ 83 , 84 ] and affect mood and memory; both Gabra4 and Gabra5 were increased after irradiation, although the former was only increased following 30 Gy. The Gls gene, which encodes for the glutaminase that is the main glutamate-producer enzyme in the brain, was downregulated in the mice treated with either 20 Gy or 30 Gy, similar to other findings in neurodegenerative disease [ 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Shank3 gene expression was significantly increased following 20 Gy, which could suggest increased neurotransmission [ 82 ]. Gabra4 and Gabra5 both contribute to inhibitory synapses signaling in neurons [ 83 , 84 ] and affect mood and memory; both Gabra4 and Gabra5 were increased after irradiation, although the former was only increased following 30 Gy. The Gls gene, which encodes for the glutaminase that is the main glutamate-producer enzyme in the brain, was downregulated in the mice treated with either 20 Gy or 30 Gy, similar to other findings in neurodegenerative disease [ 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned previously, inhibitory neurotransmission dysfunction in developmental behavioural and psychiatric disorders is well-established [ 36 ]. Clinical studies and animal models have shown that dysfunction may involve reduced levels of inhibitory neurotransmitters in cerebro-spinal fluid [ 330 , 331 ], the GABA and/or glycine receptors (reduced expression levels or loss-of-function mutations) [ 332 , 333 , 334 ], reduced inhibitory circuit inputs [ 335 , 336 , 337 ] and altered chloride channel expression [ 338 , 339 , 340 , 341 ]. In cerebral palsy, there is evidence of decreased GABA-A receptors in the cerebrospinal fluid [ 342 ] and reduced GABA receptor expression in the brainstem, but not the cortex (a further nail in the coffin of the cerebral primacy of the aetiology) [ 343 ], deficits in reciprocal inhibition [ 344 , 345 , 346 ], suggestions of reduced cortical inhibition [ 347 , 348 ] and a relationship between the of loss of inhibition and the degree of physical motor dysfunction [ 349 ].…”
Section: Inhibitory Influences On Spastic Cerebral Palsymentioning
confidence: 99%
“…Mutations in Cys-loop receptors belong to one of the best studied causes of epilepsy. In the case of GABAA receptors, monogenic GABR mutations are clustered according to their pathomechanism which can either affect channel transcription or translation, trafficking, folding, truncation, ER retention, negative effect on other subunits or lack of endogenous modulation ( Hernandez and Macdonald, 2019 ; Vogel et al, 2022 ). It has been proposed that among paralog subunits, variations in the same structural section of the protein potentially cause similar functional deficiencies due to the high homology.…”
Section: Emerging Roles Of Cys-loop Receptors In the Target Space Of ...mentioning
confidence: 99%
“…So far, mutations in GABAAR subunits α1, β2, β3, γ2, δ and ε have been associated with GESs ( Dibbens et al, 2009 ; Kang and Macdonald, 2009 ; Johannesen et al, 2016 ; Hamdan et al, 2017 ; Møller et al, 2017 ; Markus et al, 2020 ; Ahring et al, 2022a ) but more mutated GABR genes were found in patients with epilepsy, such as α2, α4, α5 and β1 ( Allen et al, 2013 ; Lien et al, 2016 ; Butler et al, 2018 ; May et al, 2018 ; Vogel et al, 2022 ). The subunits encoded by GABR genes found relevant in epilepsies contribute to receptors which mediate both phasic and/or tonic inhibition ( Guazzi and Striano, 2019 ).…”
Section: Emerging Roles Of Cys-loop Receptors In the Target Space Of ...mentioning
confidence: 99%
See 1 more Smart Citation